2005
DOI: 10.1111/j.0022-202x.2004.23599.x
|View full text |Cite
|
Sign up to set email alerts
|

Organization of Stem Cells and Their Progeny in Human Epidermis

Abstract: Renewal of epidermis is achieved by an ordered replication of stem cells and transit amplifying cells followed by terminal differentiation. In mouse epidermis, renewal is organized around highly ordered structures termed epidermal proliferative units (EPU), each generated by a single stem cell. It has been difficult to apply these concepts to the human epidermis where the basal layer is undulating and the strata have variable thickness. For example, it is unclear whether stem cells in human epidermis are locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
104
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(112 citation statements)
references
References 27 publications
7
104
1
Order By: Relevance
“…A dispersed distribution of stem cells would assist in this type of recovery. Our finding that LRCs are dispersed individually support the last possibility and agrees with several in vivo studies in which IFE healing was facilitated by dispersed epidermal stem cells [8,12,33].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A dispersed distribution of stem cells would assist in this type of recovery. Our finding that LRCs are dispersed individually support the last possibility and agrees with several in vivo studies in which IFE healing was facilitated by dispersed epidermal stem cells [8,12,33].…”
Section: Discussionsupporting
confidence: 91%
“…Although expression patterns of ␤1 high MCSP high and ␣6 high CD71 low did not overlap, long-lived and highly clonogenic cells were present in both populations, suggesting that stem cells in the IFE may not be restricted to either of these two sites. Grafting LacZmarked human keratinocytes onto immune-deficient mice or infecting the keratinocytes directly on the backs of nude mice supported evidence that stem cells were intermittently distributed throughout the basal layer of human IFE [12,14,15].…”
Section: Introductionmentioning
confidence: 87%
“…These sites in the basal layer probably contained stem cells, which play an essential role in the supply of gingival epithelial cells. Ghazizadeh et al (5) reported that stem cells were sparsely present along the basal compartment, and not in a certain limited area in the basal layer and each column generated by a single stem cell was called an "epidermal proliferative unit (EPU)". Furthermore, they observed that the widths of these columns vary considerably, with the narrowest one originating from the cells located at the base of the rete ridges.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the epidermis, there are stem cells that divide and generate themselves and transient amplifying cells, and then terminally differentiate after a discrete number of cell divisions (1)(2)(3). Such renewal has been shown to be concentrated around highly ordered structures termed epidermal proliferative units (EPU), each generated by a single stem cell (4,5). Similar to that in the epidermis, there might be proliferative units for renewal of the oral mucosal epithelium, however it is yet to be reported.…”
Section: Introductionmentioning
confidence: 99%
“…This notion was supported by the fact that integrin dull cells were more mobile on type IV collagen than integrin bri cells. However, following the fate of genetically marked cells in human epidermis has suggested instead that stem cells are scattered all along the basal layer, giving rise to cells that migrate solely upwards, forming columns of cells reminiscent of epidermal proliferative unit (EPU)-like structures [116].…”
Section: Stratified Squamous Epitheliamentioning
confidence: 99%